Production of Arthrospira platensis algae to increase production efficiency and enhance immune system of grass carp, Ctenopharyngodon idella against Aeromonas hydrophila - Hossein Adineh (تغذیه آبزیان)
Introduction: Spirulina is a unicellular and filamentous blue-green algae that has gained considerable popularity in the health food industry and increasingly as a protein and vitamin supplement to aquaculture diets. It has long been used as a dietary supplement by people living beside the alkaline lakes, where it is naturally found. Spirulina has been used as a complementary dietary ingredient of feed for fish, shrimp and poultry. Among the various species of Spirulina, the blue green algae, Spirulina platensis has drawn more attention because it shows a high nutritional content characterized by 70% protein content and by the presence of minerals, vitamins, amino acids, essential fatty acids, etc. Spirulina is used because of its bioactive compounds that are able to enhance fish growth, protect against diseases, strengthen the immune system, stimulate hunger and enhance feed consumption, reduce stress and improve digestion by increasing secretion of different digestive enzymes. It also exhibits antimicrobial and antiviral properties. In the present study, we examined the effect of blue-green algae Spirulina platensis biomass on growth performance, secretions of digestive enzymes, blood physiological indices and resistance of grass carp, Ctenopharyngodon idella infected with Aeromonas hydrophila. Materials and methods: The production of live spirulina algae was done in Arka Algae Hyrcanian Company, Golestan Province, in a greenhouse environment with 2 long pools with dimensions of 12 m long, 2.5 m wide and 50 cm height. To enrich the pool, salt at the rate of 15 g/L, sodium bicarbonate at 16 g/L, and Zaruk culture medium were used according to the manufacturer's instructions. Then, 10 to 14 days after the storage of the initial stock, when the depth of the visible Secchi disc was about 2 cm, the harvesting operation was performed from the pool. To prepare the basic diet, items were prepared and ration balance was done with the UFFDA software. Chemical composition (protein, fat and ash) of formulated diet was measured according to AOAC method. Two hundred and forty fish (7.86 ± 0.47 g) were randomly distributed in 12 tanks (20 fish per 50 L). Also, together with the consumption of basic food (protein 32.29% and energy 3984.80 kcal/kg), different levels of spirulina algae were added with a concentration of 4 × 104, 5 × 104 and 6 × 104 cells/mL (S1, S2 and S3, respectively) and basic food without algae (C), daily to rearing tanks for 60 days. At the end of the test period, growth and nutritional performance, digestive enzyme activities, blood serum antibacterial activity against Aeromonas hydrophila bacteria, immune and antioxidant factors, and blood indices were measured. One-Way ANOVA test was used for data analysis and Duncan's multiple range test to check the difference in means (p<0.05). Results: The growth of fish in the treatments containing spirulina was significantly higher and the feed conversion ratio was lower compared to the control treatment. Highest protease and lipase activities were observed in S2 and S3 treatments, respectively. The highest blood serum immune response (lysozyme, complement and total immunoglobulin) was observed in S2 and S3 treatments. The lowest and highest concentrations of superoxide dismutase and malondialdehyde were obtained in the control. Bactericidal activity of fish serum was significantly higher in S2 and S3 treatments. The highest white and red blood cells, hemoglobin and hematocrit were observed at S3 treatment; meanwhile, the lowest value was obtained in the control. Conclusion: In general, physiological parameters such as growth efficiency, digestive secretions, immunity and bactericidal activity of blood serum were improved in grass carp fed with live spirulina algae with a density of 5 × 104 and 6 × 104 cells/mL.